Persiapan Laktasi pada Ibu Hamil di Puskesmas Pakuan Baru Kota Jambi - Ria Febrina (Jurnal Abdimas Kesehatan (JAK), 2022)
The World Health Organization (WHO) recommends giving exclusive breast milk (ASI) for 6 months. Breast milk is a source of nutrition with a balanced composition and adjusted to the baby's growing needs. Global exclusive breastfeeding in 2017 was 38%. WHO targets that by 2025 there will be an increase in exclusive breastfeeding by 50%. The achievement of exclusive breastfeeding in Indonesia is 65.16%, not yet reaching the target figure of 80%. Exclusive breastfeeding coverage in Jambi Province reached 68.64%, while exclusive breastfeeding coverage at Pakuan Baru Health Center was 73.04% from the target of 80%. The unachieved coverage of exclusive breastfeeding is influenced by many factors, including low knowledge of lactation management and lack of information to mothers and their families about the importance of exclusive breastfeeding. Therefore, it is necessary to provide education to increase the knowledge of mothers about exclusive breastfeeding, which is started during pregnancy. It is hoped that when the mother gives birth, the mother can breastfeed her baby exclusively. The implementation time is in July 2020. The target of this community service is pregnant women who visit the Pakuan Baru Community Health Center. Community service methods include survey and counseling approaches. The results obtained are that pregnant women understand about exclusive breastfeeding and are willing to give exclusive breastfeeding to their babies. It is recommended that the Puskesmas maintain the extension program related to exclusive breastfeeding that has been given